For What Purpose Do Undergraduates Utilize Google Classroom? - Ochayi, Onojah Amos; Olabo, Obielodan Omotayo; Aderogba, Onojah Adenike; Musiliu, Aderoju Adekola; Joshua, Adigun Boluwatife (Indonesian Journal of Multidiciplinary Research, 2021)
There are several reasons that users use different technologies, especially students in tertiary institutions. The google classroom is not left out as some lectures are been branded using this medium. This study thus investigates the purpose which undergraduate students use Google classroom for. This study employs the survey method and 250 undergraduates were purposively sampled. The findings established that the majority of undergraduates use Google Classroom for their learning activities. There was a significant difference among undergraduate students’ purpose of utilizing google classroom based on their Academic level but not gender. The study concluded that if Google classroom is employed by lecturers for instructional activities, students are ready to utilize it. It was however recommended that curriculum developers must be well-informed and see the importance of the integration of Google classroom in the school curriculum because it may affect everyone beyond the classroom environment.